SYPHILITIC INFECTION AND PLACENTAL INSUFFICIENCY - N. V. Matyskina; T. E. Taranushenko; L. D. Zykova (Акушерство, гинекология и репродукция)
The purpose. To compare pathological disorders of placenta in syphilis infection in women with forms of placental insufficiency. Materials and methods. The observation of 114 women with confirmed syphilis infection. The control group included 30 women without a history of syphilis. Pregnant women enrolled in antenatal hospitalization and delivery in a maternity hospital of the city of Krasnoyarsk. Results. According to the research results the most frequent histological changes were manifestations corresponding to utero-placental form placental insufficiency, in group I is 44.8% and II – 52.9%, against 12.5% in the control. Conclusion. The most likely pathological mechanism of development of placental disorders-insufficient infestation cytotrophoblasts mineralnych segments of the spiral arteries, with subsequent decrease in maternal blood, obliteration of the spiral arteries, hypoxia and loss of microvision epithelium.